Reducing food loss in agricultural development projects through value chain efficiency - Nash, Julie; Peña, Olivia; Galford, Gillian L.; Gurwick, Noel; Pirolli, Gillian; White, Julianna M.; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
Food loss and waste (FLW) reduces the amount of food available for distribution and consumption, decreases food security, and increases the environmental burden of food production. Combating FLW addresses the key pillars of climate-smart agriculture for farmers by increasing productivity, promoting adaption to climate change, and mitigating greenhouse gas emissions. Although studies of interventions to reduce FLW exist, almost no research systematically investigates FLW interventions across value chains or in multiple countries, most likely due to challenges in collecting and synthesizing multi-country estimates. Our research team investigated changes in FLW in projects supported by the United States Government’s global hunger and food security initiative: Feed the Future. This provided a unique opportunity to conduct ex-ante estimates of the impacts of interventions across 20 value chains in 12 countries based on interviews with United States Agency for International Development (USAID) and project staff. We provide specific examples of interventions used in each value chain and country context. The results provide an evidence base of interventions that successfully decreased FLW at multiple points along the food value chain, from upstream producer-dominated stages to downstream consumer-dominated stages. Results also show that no single FLW solution or intervention works across agriculture sub-sectors, value chain stages, and countries. Amongst the sub-sectors studied, results showed that FLW interventions directed at extensive dairy systems could provide meaningful greenhouse mitigation. In the dairy supply chain, FLW estimates ranged from 5-50% in the business-as- usual approach and declined 4-10% as a result of intervention.